A public cloud storage auditing scheme for resource-constrained clients. (2016) - Shen, Wenting; Yu, Jia; Hao, Rong; Wang, Xuan
Cloud storage is becoming more and more popular with the development of cloud computing technique. Cloud storage auditing, as one important security service, is used to check the integrity of the cloud data stored in cloud for users. However, the burden for users to generate authenticators is very huge before cloud data are outsourced to cloud in public cloud storage auditing, especially for resource-constrained clients. In order to deal with this problem, we propose a public cloud storage auditing scheme with lightweight authenticator generation. We design a new framework of public cloud storage auditing, in which an authenticators generation centre (AGC) is in charge of generating authenticators for users. In our proposed scheme, the AGC does not know the real cloud data of users because it only generates the authenticators for blinded cloud data. To reduce the computation burden at user side, the cloud can verify whether the authenticators generated by the AGC are correct or not. As a result, the users only consume very little computation for public authenticator generation and verification. In addition, our scheme can preserve data privacy and perform batch auditing. The security analysis and the performance analysis show the proposed scheme is secure and efficient.